Clock buffer with supply noise active compensation for reduced period jitter. Issue 18 (1st August 2013) - Ravezzi, L.
Abstract : A simple circuit that actively compensates supply noise and reduces period jitter in CMOS clock buffers is presented. The locally sensed supply noise modulates a current injected in the buffer output node during transitions. By injecting the current in opposite phase to the supply noise, the transient variations are counterbalanced and the jitter removed. Designed in a 28 nm CMOS technology, a chain of 16 inverters using the proposed circuit shows a period jitter up to three times smaller than that of an equally long chain of basic inverters. Conventional local supply noise filtering would require approximately 70 times the area used by the proposed circuit to achieve similar performance.